2018
DOI: 10.3390/molecules23030685
|View full text |Cite
|
Sign up to set email alerts
|

Thiazoles and Thiazolidinones as COX/LOX Inhibitors

Abstract: Inflammation is a natural process that is connected to various conditions and disorders such as arthritis, psoriasis, cancer, infections, asthma, etc. Based on the fact that cyclooxygenase isoenzymes (COX-1, COX-2) are responsible for the production of prostaglandins that play an important role in inflammation, traditional treatment approaches include administration of non-steroidal anti-inflammatory drugs (NSAIDs), which act as selective or non-selective COX inhibitors. Almost all of them present a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 94 publications
(102 reference statements)
2
58
0
2
Order By: Relevance
“…In the aforementioned context, the darbufelone-NSAID, a dual inhibitor targeting COX-2 and 5-lipoxygenase (5-LOX), presents interest for study as a possible potential anticonvulsant. Darbufelone belongs to 4-thiazolidinone derivatives, and among this class of heterocycles, the thiazole-4-thiazolidinone hybrid molecules are known as an important source of drug-like molecules with various kinds of biological activities as well as polypharmacological agents [24][25][26][27][28][29]. The thiazole-4-thiazolidinone-bearing hybrids with promising anticonvulsant properties were identified and reported [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…In the aforementioned context, the darbufelone-NSAID, a dual inhibitor targeting COX-2 and 5-lipoxygenase (5-LOX), presents interest for study as a possible potential anticonvulsant. Darbufelone belongs to 4-thiazolidinone derivatives, and among this class of heterocycles, the thiazole-4-thiazolidinone hybrid molecules are known as an important source of drug-like molecules with various kinds of biological activities as well as polypharmacological agents [24][25][26][27][28][29]. The thiazole-4-thiazolidinone-bearing hybrids with promising anticonvulsant properties were identified and reported [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has demonstrated its anti-inflammatory properties, including the airway inflammation, with a potency comparable to clinically used drugs (Zileuton and Ketotifen), in several in vitro and in vivo studies [2][3][4][5][6][7][8][9]. The dual COX-2/5-LOX inhibition activity of tHGA makes it a promising anti-inflammatory and anti-allergic drug with fewer adverse effects [10].…”
Section: Introductionmentioning
confidence: 89%
“…It is well known that oxidative stress promotes modification of lipid metabolism [ 34 , 73 , 74 ]. Oxidative conditions have been shown to promote the activation of enzymes such as phospholipase, cyclooxygenases (COX), lipoxygenases (LOX), and cytochrome p450 (CYP450) [ 75 ], which are involved in the metabolism of lipids and their derivatives, resulting in the formation of eicosanoids, which are, in turn, involved in modulation of the redox balance and inflammation by activating specific receptors. Phospholipids are also metabolized by N-acyltransferase (NAT), phospholipase C (PLC), diacylglycerol lipase (DAGL), and N-acylphosphatidylethanolamine phospholipase D (NAPE-PLD) into endocannabinoids ( Figure 5 ) [ 76 , 77 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main substrate of cyclooxygenases is arachidonic acid (AA), which is released from phospholipids by phospholipase A 2 [ 75 ]. Due to COX activity, AA is metabolized into two-series eicosanoids, initially resulting in the formation of prostaglandin G 2 (PGG 2 ), which is subsequently reduced to PGH 2 , after which it is rapidly converted to other prostaglandins (e.g., PGE 2 , PGF 2 , PGD 2 , PGI 2 ) and thromboxanes (e.g., thromboxane A 2 ) via specific prostaglandin and thromboxane synthases [ 102 ].…”
Section: Literature Reviewmentioning
confidence: 99%